RED GINGER (Zingiber officinale var. rubrum): ITS CHEMICAL CONSTITUENTS, PHARMACOLOGICAL ACTIVITIES AND SAFETY - Rini Daud Supu; Ajeng Diantini; Jutti Levita (FITOFARMAKA: Jurnal Ilmiah Farmasi, 2018)
Ginger (Zingiber officinale) which belongs to the Zingiberaceae family, was first cultivated in Asia (Indonesia and Malaysia). This plant is one of the most commonly used herbal supplements taken by many patients to treat various conditions. Z.officinale has three varieties based on its size, colors of rhizome and chemical constituents i.e. .Z. officinale var. officinale (big white ginger or giant ginger, badak or gajah), Z. officinale var. amarum (small white ginger, emprit), and Z. officinale var. rubrum (small red ginger, merah or beureum). These three varieties may partly be deferred from their essential oil contents and are used for different purposes. The essential oils contained in Z. officinale var. rubrum are higher than the other types of ginger, which makes stronger in its pungency smell and taste. There are many studies that confirm beneficial effects of red ginger against the symptoms of diseases, i.e. anti-inflammation, antioxidant, antiemetic, antibacterial and antidiabetics. Z.officinale var. rubrum is considered to be a safe herbal medicine with only few and insignificant adverse/side effects. Although the medicinal properties of red ginger have been known, further trials in humans are required to determine the efficacy of red ginger (or one or more of its constituents) and to establish what, if any, adverse effects are observed.